Pseudolaguvia permaris, a new catfish from the Eastern Ghats of India (Teleostei: Sisoridae) - Vijayakrishnan, Balaji; Praveenraj, Jayasimhan; Mishra, Abhisek (Zootaxa, 2023)
Pseudolaguvia permaris, a new sisorid catfish is described from the Mahanadi River basin in Odisha, India. The new species can be distinguished from congeners in having the following combination of characters: serrated anterior margin of dorsal-fin spine, thoracic adhesive apparatus not extending beyond base of last pectoral-fin ray, caudal peduncle depth 8.6–10.2% SL, body depth at anus 15.3–20.2% SL, adipose-fin base length 13.6–18.1% SL, dorsal to adipose distance 11.4–14.4% SL, length of pectoral-fin spine 19.3–28.0% SL, length of dorsal-fin spine 16.5–20.4% SL, head width 21.6–25.9% SL and indistinct, creamish bands on the body.